2012
DOI: 10.1130/g32295.1
|View full text |Cite
|
Sign up to set email alerts
|

Global (latitudinal) variation in submarine channel sinuosity

Abstract: Current classifi cations of submarine channels and fans link channel sinuosity to gradient, and in turn to sediment caliber, with end members being high-sinuosity, low-gradient, fi negrained systems and low-sinuosity, high-gradient, coarse-grained systems. However, the most sinuous modern submarine channels, such as the Amazon, Bengal, Indus, and Zaire,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 27 publications
3
61
0
Order By: Relevance
“…A strong latitudinal dependence of the peak sinuosity of submarine channels was found by Peakall et al [4], with [4].) The dotted line represents a fitted curve to the data based on an exponential expression with a least-squares fit of R 2 = 0.64.…”
Section: Field Observations Of Sinuous Channel-levee Systemsmentioning
confidence: 75%
See 2 more Smart Citations
“…A strong latitudinal dependence of the peak sinuosity of submarine channels was found by Peakall et al [4], with [4].) The dotted line represents a fitted curve to the data based on an exponential expression with a least-squares fit of R 2 = 0.64.…”
Section: Field Observations Of Sinuous Channel-levee Systemsmentioning
confidence: 75%
“…Their study of 31 large-scale submarine channel-levee systems found that at high latitudes channel-levee systems have much lower sinuosity and are almost straight, while near the Equator channellevee systems are highly sinuous. In addition to differences in slope and sediment type, one of the possible explanations suggested by Peakall et al [4] for this relationship is that at high latitudes Coriolis forces systematically change the dynamics of turbidity currents.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both turbidite and contourite channels have been the subject of increasingly intense studies in recent years (e.g., Viana and Faugères, 1998;Wynn et al, 2007;Pyles et al, 2012;Kane et al, 2013;Rebesco et al, 2014;Sylvester and Covault, 2016). This is largely because they: (1) are long-lived features that are common on Earth"s siliciclastic continental margins (e.g., Normark, 1970;Wynn et al, 2007;Peakall et al, 2012;Kane et al, 2013;Hernández-Molina et al, 2014); (2) serve as effective conduits for the delivery of sediment and organic material into deep-water settings (e.g., Menard, 1955;Shepard and Emery, 1973;Clift and Gaedicke, 2002;Galy et al, 2007;Peakall and Sumner, 2015); and (3) are repositories for substantial amounts of coarse-grained sediments on and beyond the continental slope. In the case of turbidites these deposits have proven to be one of the most common types of deep-water reservoirs, whilst sandy contourites have great potential to act as reservoirs (e.g., McHargue et al, 2011;Stow et al, 2013;Gong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Preferential deposition on the outer banks of submarine channels has been attributed to many different flow processes, including reverse secondary flow (Keevil et al, 2006), the influence of Coriolis force on the flow (Peakall et al, 2012), and inertial forces in disequilibrium flows (Abd El-Gawad et al, 2012, Janocko et al, 2013a. The influence of Coriolis is negligible for the Y channel system as the latitude of the channel system is 4.7º N, and the Rossby number for these flows would be very large, indicating that centrifugal forces are much larger than Coriolis force (Sylvester et al, 2013).…”
Section: Phasementioning
confidence: 99%